Etika Jasa Endorsement di Media Sosial: Studi Komparatif Mazhab Al-Syafi’i dan Mazhab Maliki - St. Mutmainna; Rahman, Arif (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2023)
This research is entitled "Review of Islamic Law on Endorsement Services in Social Media (The Views of the Imams of the Al-Syafiiyyah and Al-Malikiyyah Schools, the problem is divided into several sub-problems, namely: 1) How is the Review of Islamic Law on Endorsement Services in Social Media and the main The problem in my research is how to review Islamic law on endorsement services on social media. 2) What are the views of Imam al-Malikiyyah and al-Malikiyyah. And the main problem is divided into sub-problems, how is the review of Islamic law on endorsement services on social media?, and what are the views of the imams of the madzhab al-Syafi'iiyah and al-Malikiyyah on the ethics of endorsement in social media? type of qualitative research (Library Research). Data sources use primary and secondary data sources where primary data uses the Qur'an and hadith while secondary data uses literature such as books, scientific journals in the form of theses, theses, information data and websites and uses a comparative normative approach in analyzing data. using content analysis or content analysis and drawing conclusions using the deductive method of drawing conclusions, namely taking something that is general in nature and drawn to a specific conception. The results of this study indicate that endorsement in an Islamic perspective is a form of mu'amalah that is justified, as long as all transactions are protected from prohibited things by sharia provisions, "Basically all forms of mu'amalah are permissible unless there is evidence that forbids it." in the form of muamalah based on high moral values in Islam, namely: Siddiq (true and honest), Amanah (trusted, credible), Fathanah (intelligent), Tabligh (communicative). There are still many deviant behaviors that are carried out by Endorsement Service users on Social Media. Endorsement Ethics in advertising Products that are not based on Islamic provisions, namely in terms of the goods endorsed. Thus, endorsement of Islam is a concept that strongly emphasizes moral and ethical values, no matter what religion. Because moral and ethical values are universal values, which are taught by all religions. The first two components, aqidah and morals (morals, ethics) are constant, both of which do not experience any change with the difference in time and place. While sharia is always changing according to the needs and levels of human differences, which are different.